A method for producing highly dense silicon dioxide from a highly pure silicon compound

CN122916635APending Publication Date: 2026-10-16ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510426675.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是该专利申请在步骤a)中加入了挥发性水溶性酸作为分散助剂,或者加入挥发性水溶性碱作为粘度控制剂,会引入其他金属或非金属元素杂质,从而影响产物二氧化硅的纯度

Benefits of technology

[0029] This process, with its simplified raw materials (including silicon compounds and ultrapure water) and controllable industrial flow, solves the problems of insufficient densification and introduction of metal impurities in traditional methods, and reveals the relationship between microstructure and sintering densification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916635A_ABST
    Figure CN122916635A_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing silicon dioxide from silicon-containing compounds, by optimizing the hydrolysis reaction parameters and sintering parameters, the bulk density of the product silicon dioxide is improved, and high-density silicon dioxide can be prepared, wherein the bulk density of the best dense silicon dioxide prepared can reach 1.591 g / cm 3 ; The raw materials used in the preparation method of the present application only include silicon-containing compounds and ultrapure water, without introducing other impurities, high-purity quartz sand suitable for the field of semiconductor preparation can be prepared, and the production process is simple, the equipment is simple, and the industrialized production of SiO2 is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicon dioxide preparation technology, and specifically to a method for preparing high-density silicon dioxide from high-purity silicon-containing compounds. Background Technology

[0002] High-purity quartz sand is widely used in industries such as semiconductors, photovoltaics, optical communications, and military applications, playing a vital and irreplaceable role in these high-tech industries due to its unique properties. In particular, the growth of silicon single crystals required by the photovoltaic and semiconductor industries relies on quartz crucibles. These crucibles mainly consist of inner, middle, and outer layers. The inner layer has the highest purity requirement for the quartz sand, demanding a purity of no less than 99.999%, and low hydroxyl content and resistance to crystallization. Crucibles made with high-quality, high-purity quartz sand typically have virtually no bubbles on their inner surface before use, and bubble rupture is extremely rare during use. This ensures long-term crystal pulling (such as multiple refeeding processes) by preventing the introduction of impurities.

[0003] High-purity quartz sand can be divided into high-purity natural quartz sand and high-purity synthetic quartz sand. High-purity natural quartz sand is mainly obtained by further purification of natural quartz ore. Previously, crucibles and fixtures used in semiconductor manufacturing were made from quartz powder obtained by crushing and purifying natural quartz. Existing quartz sand purification technologies still face the challenge of purifying quartz sand to 99.999% purity. Furthermore, high-quality quartz ore is very scarce, and matching appropriate purification technologies to different ore sources is also a major bottleneck. Therefore, not relying on quartz ore resources may be the future direction for the quartz sand industry.

[0004] In the field of synthetic silica sand, existing silica preparation technologies are mostly used to prepare nanoscale ultrafine silica powder, including gas phase synthesis, chemical precipitation, sol-gel method and microemulsion method.

[0005] The sol-gel method is widely used in SiO2 synthesis. Specifically, it uses tetraethoxysilane (TEOS) as a raw material and ethanol or methanol as a solvent. Acid or base catalyzes the hydrolysis and condensation reactions of TEOS to form a SiO2 gel, which is then washed, dried, and calcined to obtain SiO2 powder. This method offers mild reaction conditions and produces SiO2 with high purity, uniform particle size, and minimal agglomeration. However, the main drawbacks of the sol-gel method are the need for several hours (2-240 hours) of aging time to complete particle processing and growth, high raw material costs, severe environmental pollution, and difficulty in industrialization.

[0006] For example, US Patent Application Publication No. 5236483A discloses a method for preparing silica glass articles with selected shapes using a sol-gel method. The method includes the following steps: preparing a silica-containing sol solution by hydrolyzing a silanol and mixing the hydrolyzed silanol with fine silica particles; gelling the sol solution to form a wet gel; drying the wet gel by holding it under heating conditions to form a dry gel; sintering the dry gel to seal pores in the dry gel and form a silica glass article with a selected shape; heating the silica glass article to a selected temperature greater than about 1500°C and up to about 2200°C; and holding the silica glass article at the selected temperature while maintaining the glassy form for a predetermined time period sufficient to remove silica, crystals, inclusions, microcracks, and bubbles from the silica glass article, and substantially without altering the shape of the glass article from the selected shape.

[0007] The other three methods also have their own drawbacks, making it difficult to achieve the desired, low-cost, high-purity SiO2 particles. For example, the gas-phase synthesis method can produce particles with high purity and good dispersion, but the production process consumes a lot of energy, raw materials are expensive, and the equipment requires complex technology; the chemical precipitation method, although using readily available raw materials, has a simple production process, low energy consumption, and low investment, suffers from difficulty in controlling the particle size of the product, severe hard agglomeration of SiO2 particles, and difficulty in purification; the microemulsion method, although producing uniformly dispersed particles and using simple experimental equipment, suffers from low purity due to the introduction of surfactants and is easily affected by many factors such as experimental conditions. In contrast, the hydrolysis method using silicon-containing compounds (SiCl4 / SiH4, etc.) has significant advantages: the raw material is a byproduct of polycrystalline silicon (low cost and easy to obtain), the product has high purity and low hydroxyl content, but its intense hydrolysis-condensation reaction makes it difficult to control the microstructure of the loose SiO2 mass, directly affecting the performance of the sintered quartz sand. Microstructure control is a key technical challenge in the preparation of semiconductor-grade high-purity quartz sand.

[0008] Previous studies have mainly focused on understanding the hydrolysis mechanism and its impact on the properties of SiO2, such as how the hydrolysis of SiCl4 controls the size, specific surface area, dispersion properties and shape of nanoparticles. There are only a few studies on how to improve the density and purity of SiO2.

[0009] The density range of silica synthesized using existing techniques is relatively wide, ranging from 0.1 g / cm³. 3 (Aerogel) up to 2.65 g / cm³ 3 The density of silica varies (from high-purity crystals) depending on the application and performance requirements. Currently, there is relatively little focus on the bulk density of amorphous silica; the tap density, which has similar properties, is typically around 1.3 g / cm³. 3about.

[0010] US Patent Application No. 5063179A discloses a method for preparing non-porous dense silica particles. The non-porous dense silica particles have a diameter of approximately 3 to 1000 micrometers, a nitrogen BET specific surface area of ​​less than 1 square meter / gram, a total impurity content of less than 50 ppm, and a metallic impurity content of less than 15 ppm. The method includes the following steps: a) forming an aqueous dispersion containing approximately 5 wt% to 55 wt% solid pyrolytic silica; b) converting the aqueous dispersion of step a) into porous particles; c) sintering the porous particles of step b) at a temperature below approximately 1200°C in an atmosphere with a water pressure of 0.2 to 0.8 atm. However, this patent application adds volatile water-soluble acids as dispersing aids or volatile water-soluble alkalis as viscosity control agents in step a), which may introduce other metallic or non-metallic element impurities, thereby affecting the purity of the silica product. Summary of the Invention

[0011] To address the aforementioned technical problems in the prior art, this invention provides a method for preparing highly dense silica from high-purity silicon-containing compounds. This method does not introduce other impurities, produces silica with high purity and good density, and is simple to prepare, facilitating the industrial production of silica.

[0012] This invention provides a method for preparing highly dense silicon dioxide from high-purity silicon-containing compounds, comprising the following steps:

[0013] S1: A high-purity silicon-containing compound and ultrapure water undergo a hydrolysis reaction to obtain a mixture a, which is then separated to obtain a solid product; wherein, the molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:30-200;

[0014] S2: Wash and dry the solid product obtained in step S1 with ultrapure water to obtain the SiO2 precursor.

[0015] S3: The SiO2 precursor is heated to 600-800°C to remove residual H2O and hydroxyl groups from the SiO2 precursor, and then heated to 900-1200°C to obtain the silicon dioxide.

[0016] Preferably, the molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:30-120. Within this ratio range, the water content in the reaction system is low, the SiO2 monomer is more uniformly dispersed, and the gel network is more tightly connected, which can form a denser microstructure.

[0017] Preferably, the molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:70. At this ratio, the SiO2 precursor achieves maximum bulk density by balancing the reduction of monomer aggregation and the maintenance of a sufficiently connected gel backbone.

[0018] Preferably, in step S3, T1 is 800°C and T2 is 1000°C. Under these conditions, the residual H2O and hydroxyl groups in the SiO2 precursor are removed more thoroughly; the SiO2 sintering temperature is higher, the pore size of the SiO2 powder is smaller, resulting in a smaller pore volume, and the formed SiO2 product is more compact, and SiO2 will not transform into α-cristobalite.

[0019] Preferably, the silicon-containing compound is tetramethoxysilane (TMOS), tetraethyl orthosilicate (TEOS), or silicon tetrachloride (SiCl4).

[0020] Preferably, the purity of the high-purity silicon-containing compound is ≥99.99%.

[0021] More preferably, the high-purity silicon-containing compound is silicon tetrachloride with a purity of ≥99.9999%.

[0022] Preferably, the hydrolysis reaction in step S1 is carried out at a temperature of 25–55°C for 3–30 hours.

[0023] Preferably, in step S1, when the silicon-containing compound is tetramethoxysilane or ethyl silicate, a hydrochloric acid solution with an HCl content of 0.4–0.7 mmol is added to the raw materials of the hydrolysis reaction. Within this range, for hydrochloric acid solutions with slightly higher concentrations, less hydrochloric acid solution is added; for hydrochloric acid solutions with slightly lower concentrations, more hydrochloric acid solution is added.

[0024] Preferably, in step S2, the solid product is first washed with ultrapure water until the pH of the washing supernatant is ≤5, then dried to obtain SiO2 powder. The obtained SiO2 powder is then washed a second time with water until the washing supernatant is neutral to remove the hydrochloric acid component from the system. It is then dried again to obtain the SiO2 precursor. Drying before the second water wash allows some of the HCl remaining inside and on the surface of the gel to evaporate under heating conditions. After drying, a simple wash makes it easier to neutralize the reaction system, thus reducing the number of washing cycles. Preferably, in step S3, the heating pressure is -0.1 MPa; the heating rate is 5–10 °C / min. -1 Heat to 600-800℃ and hold for 2-12 hours; heat to 900-1200℃ and hold for 8-10 hours.

[0025] The core principle of this patent lies in achieving the efficient conversion of high-purity silicon-containing compounds into highly dense amorphous silica through precise control of hydrolysis reaction conditions and a multi-stage sintering process. This is achieved through the following technological breakthroughs:

[0026] (1) Hydrolysis parameter optimization: The molar ratio of silicon-containing compound to ultrapure water is limited (1:30-200), especially 1:70, to achieve a balance between reducing monomer aggregation and enhancing the density of the gel network, forming a precursor with uniform pore configuration.

[0027] (2) Segmented sintering process: A two-stage heating process (600-800℃ for impurity removal and 900-1200℃ for densification), combined with precise temperature control and a negative pressure environment, effectively eliminates porosity and inhibits the formation of α-cristobalite phase, thereby increasing the bulk density of silica to 1.591 g / cm³. 3 .

[0028] (3) Purification and Activation Energy Control: Impurities were thoroughly removed through multi-stage washing (alternating between weak acid and neutral solutions). Guided by TG-DSC analysis, the heat treatment conditions for sintering densification were determined. A combination of characterization techniques, including FTIR, XRD, SEM, TEM, and BET, confirmed that sintering effectively collapsed the pores, significantly reduced the specific surface area, and increased the bulk density of SiO2. The highest bulk density after sintering was 1.591 g / cm³. 3 Under these hydrolysis parameters, the sintering activation energy of the SiO2 precursor is the lowest (34.439 kJ·mol⁻¹), which facilitates local particle flow, boundary migration, and pore collapse, all of which contribute to the densification of SiO2. This ultimately yields dense amorphous silicon dioxide with low specific surface area and high purity, suitable for precision applications such as semiconductors.

[0029] This process, with its simplified raw materials (including silicon compounds and ultrapure water) and controllable industrial flow, solves the problems of insufficient densification and introduction of metal impurities in traditional methods, and reveals the relationship between microstructure and sintering densification. Attached Figure Description

[0030] Figure 1 Infrared spectra of SiO2 precursors under different hydrolysis parameters in Examples 1-7;

[0031] Figure 2 The infrared contrast spectrum of SiO2 before and after sintering in Example 3 is shown below.

[0032] Figure 3 The images show the XRD patterns of SiO2 before and after sintering under different hydrolysis parameters in Examples 1-7.

[0033] Figure 4 The images show the TG-DSC diagrams of the SiO2 precursor under different hydrolysis parameters in Examples 1-7.

[0034] Figure 5 SEM images of the SiO2 precursors from the hydrolysis reaction in Examples 2-4;

[0035] Figure 6 SEM images of highly dense SiO2 after sintering in Examples 2-4;

[0036] Figure 7 The figures show the nitrogen adsorption curves of SiO2 before and after sintering under different hydrolysis parameters in Examples 1-7.

[0037] Figure 8 The graph shows a comparison of the BET specific surface area before and after heat treatment under different hydrolysis parameters in Examples 1-7.

[0038] Figure 9 The figures show the pore size distribution of SiO2 before and after sintering under different hydrolysis parameters in Examples 1-7.

[0039] Figure 10 Comparison of bulk density and activation energy before and after sintering under different hydrolysis parameters in Examples 1-7;

[0040] Figure 11 The image shows the XRD pattern of SiO2 after sintering in Comparative Example 1. Detailed Implementation

[0041] Example 1

[0042] Step 1: Prepare 40 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 8 mL of 99.9999% SiCl4 dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. Connect the other neck of the two-necked flask to a beaker containing sodium hydroxide solution to absorb the hydrogen chloride tail gas produced in the reaction. The entire reaction is controlled at 25°C using an insulated water bath (IKA). At this temperature, the molar ratio of SiCl4 to H2O is 1:30.

[0043] Step 2: After the continuous injection phase, continue stirring for 3 hours to complete the reaction. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 110℃ for 5 hours to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component in the system. Dry the washed solid product in a forced-air oven at 110℃ for 10 hours to obtain the SiO2 precursor.

[0044] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0045] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 600℃ at a certain rate and held for 2 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0046] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 900℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0047] Example 2

[0048] Step 1: Prepare 60 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 8 mL of 99.9999% SiCl4 dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. Connect the other neck of the two-necked flask to a beaker containing sodium hydroxide solution to absorb the hydrogen chloride tail gas produced in the reaction. The entire reaction is controlled at 30°C using an insulated water bath (IKA). At this temperature, the molar ratio of SiCl4 to H2O is 1:50.

[0049] Step 2: After the continuous injection phase, continue stirring for 5 hours to complete the reaction. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 100℃ for 8 hours to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component in the system. Dry the washed solid product in a forced-air oven at 100℃ for 10 hours to obtain the SiO2 precursor.

[0050] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0051] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 700℃ at a certain rate and held for 5 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0052] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1100℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0053] Example 3

[0054] Step 1: Prepare 90 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 8 mL of 99.9999% SiCl4 dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. Connect the other neck of the two-necked flask to a beaker containing sodium hydroxide solution to absorb the hydrogen chloride tail gas produced in the reaction. The entire reaction is controlled at 25°C using an insulated water bath (IKA). At this temperature, the molar ratio of SiCl4 to H2O is 1:70.

[0055] Step 2: After the continuous injection phase, continue stirring for 8 hours to complete the reaction. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 90°C for 8 hours to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component in the system. Dry the washed solid product in a forced-air oven at 90°C for 10 hours to obtain the SiO2 precursor.

[0056] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0057] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 800℃ at a certain rate and held for 2 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0058] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1000℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0059] Example 4

[0060] Step 1: Prepare 120 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 8 mL of 99.9999% SiCl4 dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. Connect the other neck of the two-necked flask to a beaker containing sodium hydroxide solution to absorb the hydrogen chloride tail gas produced in the reaction. The entire reaction is controlled at 30°C using an insulated water bath (IKA). At this temperature, the molar ratio of SiCl4 to H2O is 1:100.

[0061] Step 2: After the continuous injection phase, continue stirring for 8 hours to complete the reaction. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 100℃ for 10 hours to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component in the system. Dry the washed solid product in a forced-air oven at 100℃ for 10 hours to obtain the SiO2 precursor.

[0062] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0063] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 800℃ at a certain rate and held for 2 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0064] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1100℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0065] Example 5

[0066] Step 1: Prepare 90 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 6.5 mL of TMOS (99.99%) dropwise into the ultrapure water at a rate of 20 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. The entire reaction is controlled at 45°C using an insulated water bath (IKA). At this temperature, the molar ratio of TMOS to H2O is 1:120.

[0067] Step 2: After the continuous injection phase, add 0.8 mL of 5M hydrochloric acid solution dropwise from the other end of the two-necked flask to promote the hydrolysis and condensation rate of TMOS. Continue stirring for 20 h to complete the reaction. This is because, compared with silicon tetrachloride hydrolysis, the TMOS reaction system lacks an acidic medium, resulting in a slower reaction process and making it more difficult to form a complete network structure. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 80℃ for 8 h to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component from the system. Dry the washed solid product in a forced-air oven at 100℃ for 10 h to obtain the SiO2 precursor.

[0068] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0069] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 600℃ at a certain rate and held for 12 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0070] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1200℃ at a heating rate, held for 8 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0071] Example 6

[0072] Step 1: Prepare 120 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 9 mL of TEOS (99.99%) dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. The entire reaction is controlled at 55°C using an insulated water bath (IKA). At this temperature, the molar ratio of TEOS to H₂O is 1:150.

[0073] Step 2: After the continuous injection phase, add 1.3 mL of 5M hydrochloric acid solution dropwise from the other end of the two-necked flask to promote the hydrolysis and condensation rate of TEOS. Continue stirring for 15 h to complete the reaction. This is because, compared with silicon tetrachloride hydrolysis, the TEOS reaction system lacks an acidic medium, resulting in a slow reaction process and difficulty in forming a complete network structure. Wash the solid product of the reaction three times with ultrapure water by centrifugation until the pH of the washing supernatant is ≤5. Remove the washing supernatant and dry the washed solid product in an oven at 80℃ for 8 h to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component from the system. Dry the washed solid product in a forced-air oven at 100℃ for 10 h to obtain the SiO2 precursor.

[0074] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0075] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 800℃ at a certain rate and held for 12 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0076] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1000℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0077] Example 7

[0078] The difference between this embodiment and Embodiment 6 is that, in step 1, the volume of TEOS is 6 mL and the volume of ultrapure water is 100 mL. At this time, the molar ratio of TEOS to H2O is 1:200; in step 2, 2 mL of 5M hydrochloric acid is added dropwise, and the mixture is stirred continuously for 30 h to complete the reaction.

[0079] Comparative Example 1

[0080] Step 1: Prepare 90 mL of ultrapure water in a two-necked flask. Using a syringe pump, add 8 mL of 99.99% SiCl4 dropwise to the ultrapure water at a rate of 30 mL / h. Use a magnetic stirrer to control the reaction speed at 250 rpm to ensure the reaction solution is thoroughly mixed. Connect the other neck of the two-necked flask to a beaker containing sodium hydroxide solution to absorb the hydrogen chloride tail gas produced in the reaction. The entire reaction is controlled at room temperature (30°C) using an insulated water bath (IKA). At this point, the molar ratio of SiCl4 to H2O is 1:120.

[0081] Step 2: After the continuous injection phase, continue stirring for 8 hours to complete the reaction. Wash the solid product three times with ultrapure water by centrifugation to obtain a weakly acidic wash supernatant with pH ≤ 5. Remove the wash supernatant and dry the washed solid product in an oven at 80°C for 8 hours to obtain SiO2 powder. Wash the SiO2 powder a second time with water and centrifuge twice with ultrapure water until the supernatant is almost neutral to remove the hydrochloric acid component in the system. Dry the washed solid product in a forced-air oven at 100°C for 10 hours to obtain the SiO2 precursor.

[0082] Step 3: Transfer the SiO2 precursor powder into a 10mm diameter room temperature pressing mold and apply 100MPa pressure to press it into a cylindrical block.

[0083] Step 4: Place the pressed block into an alumina crucible and sinter it in a tube furnace. The specific sintering procedure is as follows: evacuate the alumina tube to a negative pressure, maintain the pressure inside the tube at -0.1 MPa, and sinter at 10°C / min. -1 The temperature was increased to 600℃ at a certain rate and held for 12 hours to remove residual H2O and hydroxyl groups from the SiO2 precursor powder.

[0084] Step 5: The SiO2 precursor powder with H2O and hydroxyl groups removed is further subjected to densification heat treatment at 5℃ for 5 min. -1 The temperature was increased to 1300℃ at a heating rate, held for 10 hours, and then cooled to room temperature in the furnace to obtain a high-density SiO2 product.

[0085] Detection Example 1

[0086] The microstructure of silica in Examples 1-7 and Comparative Example 1 was characterized, and the results are as follows:

[0087] Figure 1 The images show the infrared spectra of the SiO2 precursors in Examples 1-7. The infrared spectra of samples from different examples are similar, with the corresponding peak positions being consistent. The 460 cm⁻¹ peak is also present. -1 The nearby peak is the bending vibration peak of Si-O-Si, 779 cm⁻¹. -1The nearby peak is a symmetric stretching vibration peak of Si-O-Si, at 940 cm⁻¹. -1 The nearby peak is the bending vibration peak of Si-OH, 1098 cm⁻¹. -1 The nearby peak is an antisymmetric stretching vibration peak of Si-O-Si, which appears as a broad and intense peak in the spectrum. (1630 cm⁻¹) -1 The nearby peak is the bending and stretching vibration peak of water's HOH, at 3445 cm⁻¹. -1 The nearby peaks are antisymmetric stretching vibration peaks caused by Si-OH.

[0088] Figure 2 The image shows the infrared contrast spectrum of SiO2 before and after sintering in Example 3. After heat treatment, the wavenumber in its infrared spectrum is around 1630 cm⁻¹. -1 940cm -1 and 3445cm -1 The intensity of nearby peaks decreased significantly, or even disappeared completely, indicating that the hydroxyl groups evaporated in the form of water molecules. Furthermore, infrared spectroscopy is also an indicator of purity and can be used to assess the purity of the product prepared by this method. In the example, all characteristic peaks corresponding to the functional groups of the target substance were clearly visible in the red light spectrum, and the peak positions were consistent with the standard spectrum. Figure 1 The peaks are symmetrical and sharp, which can eliminate peak distortion caused by impurities or intermolecular interactions. Except for the characteristic peaks of silica, the spectrum has a smooth baseline and no obvious impurity peaks, spikes or unknown absorption bands. The above characteristics indicate that the silica prepared in the example exhibits high purity.

[0089] Figure 3 The XRD patterns of the silica samples prepared in Examples 1-7 are shown. First, from... Figure 3 As can be seen in (a) of the diagram, the crystal morphology of the SiO2 precursors obtained from different embodiments remained almost unchanged, and the diffraction peaks of the SiO2 powders were all located at 22°, consistent with the standard amorphous SiO2 (JCPDS29-0085) card, proving that the obtained product was amorphous SiO2 powder without any other impurities. Furthermore, Figure 3 (b) shows the relationship with Figure 3 The similar spectral distribution in (a) indicates that the sintered silica sample retains its amorphous state after sintering. When the green silica sample was sintered at the temperature (1300℃) of Comparative Example 1, the α-cristobalite phase ( Figure 11 Its XRD pattern shows a sharp diffraction peak at 21.9°, which is significantly different from the broadened and diffuse peaks of amorphous silica, and is a typical characteristic of α-cristobalite phase.

[0090] To determine the thermodynamic properties of the SiO2 precursor obtained from the hydrolysis of silicon-containing compounds, we performed thermal analysis on the samples synthesized in Examples 1-7. Figure 4 As shown in (a), the total mass loss of the SiO2 precursor was approximately 12% after heating to 1300 °C. First, a significant mass loss occurred near 150 °C, primarily due to the removal of H2O. Second, the mass continued to decrease between 150 °C and 800 °C, likely due to the continued polymerization of the SiO2 network and the removal of surface -OH groups, consistent with the weakening or absence of -OH-related infrared peaks in the sintered sample. From 800 °C to 1200 °C, the sample mass remained almost constant, while a slight mass increase (approximately 0.5%) occurred above 1200 °C, possibly due to the transformation of amorphous SiO2 to α-cristobalite occurring in the 1200–1300 °C range. Furthermore, differential scanning calorimetry (DSC) data showed an endothermic peak near 100 °C. Figure 4 (b) reflects the release of adsorbed H2O, followed by a wider exothermic peak in the temperature range of 1200-1300℃, marking the beginning of crystalline phase formation. Based on these findings, 1200℃ is considered the critical temperature for sintering and densification, preventing the transformation of amorphous SiO2 into α-cristobalite. Otherwise, the transformation into α-cristobalite might compromise the optical transparency and mechanical reliability of the final SiO2 glass.

[0091] To reveal the relationship between morphology and sintering performance, the morphology of samples before and after sintering was observed and analyzed using scanning electron microscopy (SEM). Images of the morphology before sintering are shown below. Figure 5 As shown, at low water content (molar ratio of silicon compound to ultrapure water is 1:50), the SiO2 precursor exhibits a non-uniform agglomerated blocky distribution. Figure 5 (a) This is because the low dispersibility of the reaction system leads to monomer aggregation, resulting in larger particle sizes. As the water content in the reaction increases, the dispersibility of the reaction system gradually improves, alleviating monomer aggregation. Simultaneously, due to the rapid reaction of SiCl4 with water, the reactant monomers tend to polymerize, and the reaction product gradually develops into a gel structure with a certain porosity. Figure 5 As can be seen in (b), the SEM image of the SiO2 precursor obtained in Example 3 changes from an aggregated mass to an interconnected skeletal structure. The SEM image of the SiO2 precursor obtained in Example 4 is mainly dominated by a gel framework structure. Figure 5 (c) in the middle.

[0092] SEM images of sintered SiO2 particles ( Figure 6 The sample is significantly more compact and flat than the unsintered sample. This is because the SiO2 network skeleton is tightly connected after sintering, the porosity is reduced, and the compactness of the SiO2 particles is improved.

[0093] To gain a more comprehensive understanding of the sample's microstructure, we conducted BET tests on the sample before and after sintering. Figure 7 Figure (a) in 7 and Figure (b) in 7 show the N adsorption-desorption isotherms of SiO2 powder before and after sintering in different embodiments. Figure 7 In (a) of the table, the N adsorption-desorption isotherms of the precursor samples from Examples 1-4 exhibit typical Type III behavior, while the N adsorption-desorption isotherms of the precursor samples from Examples 5-7 exhibit typical Type IV behavior. With increasing H₂O content, the hysteresis loop gradually transitions from Type III to Type IV. This is likely because, with increasing H₂O content, the porosity of the SiO₂ powder gradually changes from a mixture of macropores and mesopores to being predominantly mesopores. After sintering, the N adsorption-desorption isotherms of all samples exhibit typical Type IV characteristics, which is characteristic of mesoporous materials, indicating that heat treatment is an important method for reducing the porosity and increasing the density of SiO₂ powder. The shape of the hysteresis loop is generally related to the specific pore structure.

[0094] BET specific surface area tests were performed on SiO2 powders before and after sintering. Figure 8 As shown, the specific surface area of ​​the precursor samples in Examples 1-7 gradually increases. This is mainly because the increase in solvent during the reaction process enhances the dispersibility of the reaction system, gradually reducing the degree of monomer aggregation, thereby leading to a gradual decrease in particle size. The specific surface area of ​​the sintered samples decreases significantly, possibly because the pores inside SiO2 tend to shrink and collapse during high-temperature sintering. This structural change makes the original porous structure more compact, thus reducing the specific surface area of ​​SiO2.

[0095] To further verify the effect of the sintering process on SiO2 densification, the pore size distribution (PSD) of all samples before and after sintering was measured. The PSD of the precursor samples is shown below. Figure 9 As shown in (a), the precursor samples of Examples 1-4 have pore sizes distributed between 2-10 nm and 10-50 nm, while the precursor samples of Examples 5-7 have pore sizes mainly distributed between 2-5 nm, which corresponds to the material indicated by their hysteresis rings. From Figure 9 As can be clearly seen in (b), the pore size of most of the sintered samples is between 3-4 nm, which corresponds to mesoporous materials. Furthermore, the peak pore volume of the sintered samples is lower than that of the green sample. This is because as the sintering temperature increases, the pore size of the SiO2 powder decreases, leading to a reduction in pore volume. The pressure generated by solvent evaporation at high temperatures makes the internal pores more prone to shrinkage and collapse, resulting in smaller pore size and reduced pore volume.

[0096] To evaluate the improvement in SiO2 density after sintering, the bulk density of the green sample and the sintered sample was tested. Figure 10(a) Specific data are shown in Table 1. Before sintering, the volumetric density of SiO2 in Example 3 reached its peak. When the H2O concentration is relatively low, the hydrolysis reaction tends to produce agglomerates of uneven size due to the uneven aggregation and dispersion of SiO2 monomers. These larger agglomerates trap pores during tableting, thus limiting particle stacking and reducing volumetric density. In contrast, at higher H2O concentrations, the dispersibility of the reaction system improves, forming a looser gel structure. Under the same tableting conditions, this loose arrangement again leads to a lower compacted volumetric density. Therefore, under the hydrolysis parameters of Example 3, the SiO2 precursor achieves maximum volumetric density by balancing reduced monomer aggregation with maintaining a sufficiently connected gel backbone. Under these hydrolysis parameters, the dispersibility of the reaction system is moderate, the degree of agglomeration is alleviated, and the gel network is tightly connected, resulting in a denser microstructure.

[0097] After sintering, the SiO2 sample prepared in Example 3 again exhibited the highest bulk density (1.591 g / cm³). 3 To elucidate the underlying mechanism, thermal expansion tests were performed on the SiO2 precursor. Figure 10 (b) of the study, and their sintering activation energies were determined. Figure 10 (c)). When heated to 1300°C, the total dimensional shrinkage reaches 18%, covering three temperature ranges:

[0098] (1) First range (25-150℃): Shrinkage is negligible, mainly due to solvent removal;

[0099] (2) Second range (150-1200℃): Significant shrinkage occurred, attributed to the formation of additional Si-O-Si bonds through condensation reactions and the densification of the framework achieved through structural relaxation by atomic movement in the network, without further H2O expulsion;

[0100] (3) Third range (1200-1300℃): Rapid viscous sintering leads to micropore collapse.

[0101] Using this thermal expansion data, the sintering activation energy of the green sample was calculated and fitted. The fitting result of the sintering activation energy is as follows: Figure 10 As shown in (c), the sintering activation energy first decreases and then increases with increasing H2O content, reaching its lowest value at the hydrolysis parameters of Example 3. The lower activation energy promotes local particle flow, boundary migration, and pore collapse, ultimately achieving a higher bulk density. This trend in sintering activation energy is consistent with the change in bulk density after sintering, further confirming that the evolution of microstructure has a strong influence on the sintering densification process.

[0102] Table 1 Summary of densification data before and after sintering for different embodiments

[0103]

[0104] We also compared the changes in bulk density before and after sintering under different embodiments. As expected, the bulk density of the sintered samples increased, reflecting particle rearrangement, boundary diffusion, and pore collapse during sintering. At lower H2O concentrations, the hydrolysis reaction tended to produce irregular agglomerates, which could easily rearrange and form sintering necks during sintering. This promoted effective pore removal, thus significantly increasing the bulk density after sintering. In contrast, higher H2O concentrations tended to form a loosely arranged and loosely packed gel-like network structure. Although the initial collapse of these gel pores led to some increase in bulk density during sintering, the interconnected channels in the porous microstructure slowed mass transfer and limited further pore removal. Therefore, densification may be inhibited. Notably, the increase in bulk density after sintering was most significant in Example 3. This phenomenon indicates that under these hydrolysis conditions, the arrangement of agglomerates and the gel skeleton was optimal, promoting the formation of sintering necks and effective pore removal. Therefore, the densification process was significantly enhanced.

Claims

1. A method for preparing highly dense silicon dioxide from high-purity silicon-containing compounds, characterized in that, Includes the following steps: S1: High-purity silicon-containing compound and ultrapure water undergo hydrolysis to obtain mixture a, which is then separated to obtain a solid product; The molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:30-200. S2: Wash and dry the solid product obtained in step S1 with ultrapure water to obtain the SiO2 precursor. S3: The SiO2 precursor is heated to T1 to remove the residual H2O and hydroxyl groups in the SiO2 precursor, and then heated to T2 to obtain the silicon dioxide. T1 is 600-800℃ and T2 is 900-1200℃.

2. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, The molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:30-120.

3. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 2, characterized in that, The molar ratio of the high-purity silicon-containing compound to ultrapure water is 1:

70.

4. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, In step S3, T1 is 800℃; T2 is 1000℃.

5. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, The silicon-containing compound is silicon tetrachloride, tetramethoxysilane, or ethyl silicate.

6. The method for preparing highly dense silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, The purity of the high-purity silicon-containing compound is ≥99.99%.

7. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, The hydrolysis reaction in step S1 is carried out at a temperature of 25–55°C for 3–30 hours.

8. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, In step S1, when the silicon-containing compound is tetramethoxysilane or ethyl silicate, a hydrochloric acid solution with an HCl content of 0.4 to 0.7 mmol is added to the raw materials of the hydrolysis reaction.

9. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, In step S2, the solid product is first washed with ultrapure water until the pH of the washing supernatant is ≤5, and then dried to obtain SiO2 powder. The obtained SiO2 powder is washed with water a second time until the washing supernatant is neutral, and then dried again to obtain the SiO2 precursor.

10. The method for preparing high-density silicon dioxide from high-purity silicon-containing compounds according to claim 1, characterized in that, In step S3, the pressure during the heating process is -0.1 MPa; the heating rate is 5–10 °C / min. -1 Heat to 600-800℃ and hold for 2-12 hours; heat to 900-1200℃ and hold for 8-10 hours.

Citation Information

Patent Citations

  • Process for making non-porous micron-sized high purity silica

    US5063179A

  • Method of preparing silica glass

    US5236483A